ETR 300 Golden Pearl Resor t/ Nazirah Hadzam... [et al.] - Hadzam, Nazirah; Ishak, Norahan; Shahidan, Noor Faizah; Azizan, Norhafiza; Yom, Noor Zaimaina (2000)
Golden pearl resort was a partnership business that involve 5 team members. The main activities of this company are provide a chalet for customer. This company started their operation on 1 January 2003. It was located at Kuala Ketil, Kedah.